High-throughput mutation profiling of CTCL samples reveals KRAS and NRAS mutations sensitizing tumors toward inhibition of the RAS/RAF/MEK signaling cascade - Kießling, Michael; Oberholzer, Patrick A.; Mondal, Chandrani; Karpova, Maria B.; Zipser, Marie C.; Lin, William M.; Girardi, Michael; MacConaill, Laura E.; Kehoe, Sarah M.; Hatton, Charlie; French, Lars E.; Garraway, Levi A.; et al. (Blood, 2011)
Cutaneous T-cell lymphomas (CTCLs) are malignancies of skin-homing lymphoid cells, which have so far not been investigated thoroughly for common oncogenic mutations. We screened 90 biopsy specimens from CTCL patients (41 mycosis fungoides, 36 Sézary syndrome, and 13 non-mycosis fungoides/Sézary syndrome CTCL) for somatic mutations using OncoMap technology. We detected oncogenic mutations for the RAS pathway in 4 of 90 samples. One mycosis fungoides and one pleomorphic CTCL harbored a KRASG13D mutation; one Sézary syndrome and one CD30+ CTCL harbored a NRASQ61K amino acid change. All mutations were found in stage IV patients (4 of 42) who showed significantly decreased overall survival compared with stage IV patients without mutations (P = .04). In addition, we detected a NRASQ61K mutation in the CTCL cell line Hut78. Knockdown of NRAS by siRNA induced apoptosis in mutant Hut78 cells but not in CTCL cell lines lacking RAS mutations. The NRASQ61K mutation sensitized Hut78 cells toward growth inhibition by the MEK inhibitors U0126, AZD6244, and PD0325901. Furthermore, we found that MEK inhibitors exclusively induce apoptosis in Hut78 cells. Taken together, we conclude that RAS mutations are rare events at a late stage of CTCL, and our preclinical results suggest that such late-stage patients profit from MEK inhibitors.
Gesehen am 01.08.2022